TECHNIKI OBRAZOWANIALong term results of surgical treatment of the superior vena cava syndrome – a case report - Głowacki, Jan; Miszalski-Jamka, Karol; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Superior vena cava syndrome (SVCS) is caused by obstruction of the superior vena cava. Surgical treatment remains one of the therapeutic methods, especially in patients with SVCS due to non-malignant causes. We present a case of a 68-year-old female with benign SVCS treated surgically in our hospital. Computed tomography performed 14 years after the surgical intervention confirmed the patency of the bypass graft.